ISCHEMIC HEART DISEASE: PATHOLOGY AND AUTOPSY DIAGNOSIS - Band, Rahul; Rani, Yashoda; Agarwal, Shilpi; Naik, S K; Meena, Mahesh Chand (Journal of Forensic Medicine and Toxicology, 2014)
Ischemic Heart Disease [IHD] is a generic designation for a group of related syndromes resulting from myocardial ischemia. Autopsy diagnosis of acute lesion in heart, such as early myocardial infarct, can have profound medico legal implications. The basic, irreversible lesion of the myocardium in acute “coronary heart disease” is an ischemic coagulation necrosis of muscle fibers with subsequent polymorphonuclear leukocytic infiltration, granulation tissue, and scar formation. Only severe ischemia lasting at least 20 to 40 minutes causes irreversible injury and myocyte death; the predominant pattern is coagulation necrosis. With longer periods of ischemia, microvasculature injury ensues. Studies using high resolution microscope and electron microscope should be undertaken for detection of ischemic changes which are missed on routine microscopy. Various staining techniques like TTC (Triphenyl Tetrazolium Chloride), NBT (Nitro-blue tetrazolium), Masson’s trichrome, histochemical methods and Electron Microscopic Apoptotic changes can be used for detection of early ischemic changes.